O conceito de homem em Ludwig Feuerbach (a partir da crítica a religião cristã) - Costa, José Luiz Silva da (2013)
The present essay has as main objective to ransom the concept of man from the unveiling of the cristhian religion, accomplished by Ludwig Andreas Feuerbach (1804-1872), having as main work The essence of the cristhianism (1941). It will be analyzed herein the concept of man, as a plural and unabridged being and, the substantiation of such concept arising from his critic to the religion and, therefore, the foundations of what had became known as his anthropological atheism. Thus, the author of this essay is trying to demonstrate where are the latent mysteries that are hidden within the religion and, in the same way in the human mind. For this reason, the religion terminology is not discarded in the feuerbachian propositions, but formerly resignified from its real genealogy and immanent to the man. In this work it will be uncloaked the vital relation between the man and his insides, the man and the religion, the man and the nature and, lastly, the whole human life in its fortunes and setbacks. For this, Feuerbach develops a reflexion in order to demythologize the religion, as fundamental criterion for the emancipating of the man and thereby, to make him responsible for his biosphere. From then on, it is no longer about arguing the relation God and man, it is now concerning about choosing as creator or God or man. Arises there, the maxim: The Man is its God. Such that, the unilateral relation of domination of the theology over the anthropology is reduced to a relation of the anthropology with itself. It will also be highlighted herein the human attributes concealed in the religion way and deciphered in the anthropological way. In this case, the anthropological atheism dos not mean just a defeat of the objector (religion) of full human life. It, formerly, constitutes itself as a new beginning to the human odyssey, now free and emancipated